Clinicopathologic characterization of hidradenoma on acral sites: a diagnostic pitfall with digital papillary adenocarcinoma - Wiedemeyer, Katharina; Gill, Pavandeep; Schneider, Michelle; Kind, Peter; Brenn, Thomas (The American journal of surgical pathology, 2020)
Hidradenomas are benign sweat gland tumors that typically present as small nodules in adulthood. Their anatomic distribution is wide and rarely includes acral sites. In this setting, reliable separation from digital papillary adenocarcinoma is important, but notoriously difficult. Hematoxylin and eosin-stained sections of 25 hidradenomas on acral skin were retrieved. The clinical presenting features and morphologic findings were recorded, and follow-up was obtained. Immunohistochemistry was performed for AE1/3, CK5/6, EMA, CEA, SMA, S100, p40, and p63. The tumors presented as solitary nodules on the hands (n=17) and feet (n=8) of adults (age range: 20 to 81 y; median: 50 y), with an equal sex distribution. Histologically, the well-circumscribed tumors were lobular, with a solid and cystic growth within dermis. Duct and squamous differentiation and vascularized hyaline stroma were frequent. The majority (n=18) were poroid hidradenomas. Scattered cytologic atypia and mitotic activity (median: 2/10 HPF) were common, and a pseudoinfiltrative growth of strands in a hyaline to sclerotic matrix was noted in 5 tumors. No papillary structures, atypical mitoses, or tumor necrosis were present. Immunohistochemically, all tumors expressed AE1/3, CK5/6, p40, and p63 strongly and diffusely. Luminal differentiation was highlighted by epithelial membrane antigen and carcinoembryonic antigen staining. S100 and SMA staining was absent. Follow-up (1 to 288 mo; median: 61 mo), available for 20 patients, showed no local recurrences and no disease-related mortality. Acral hidradenomas and digital papillary adenocarcinomas share a well-circumscribed dermal growth pattern containing solid, cystic, and tubular areas with mitotic activity and at least focal cytologic atypia. Lack of papillary structures and the diffuse positivity for p40 and p63 in the absence of S100 and SMA expression are helpful features in favor of acral hidradenoma.